Ethical Considerations in HR: Navigating the Intersection of Technology and Human Capital - Mei Veronika Sri Endang Siagian; Sri Wiyati Mahrani; Pipit Sundari (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research delves into the complex interplay between technology integration, human capital management practices, organizational culture, and ethical decision-making within PT Tirta Investama. Through quantitative analysis using structural equation modeling, the study examines direct and indirect effects of technology integration and human capital management practices on ethical decision-making, mediated by organizational culture. The findings indicate significant direct effects of both technology integration and human capital management practices on ethical decision-making, highlighting their crucial roles in shaping ethical behaviors within the organization. Additionally, the study unveils the mediating role of organizational culture, as both technology integration and human capital management practices indirectly influence ethical decision-making through their impact on organizational culture. These findings underscore the importance of fostering a positive and ethical organizational culture aligned with technological initiatives and HR practices to promote responsible decision-making and enhance organizational sustainability.